Evaluating the Impact of the National Scheme of Incentive to Girls for Secondary Education (NSIGSE) on Gender Parity and Educational Equity in India - Arora, Alankrita (Tufts University Tisch Library, 2025)
Thesis (M.S.)--Tufts University, 2025.; Submitted to the Dept. of Economics.; Advisor: Jeffrey Zabel.; Committee: Julie Schaffner, and Jeffrey Zabel.; Keyword: Economics.